MILITARY COOPERATION IN THE FIGHT AGAINST TERRORISM FROM THE STANDPOINT OF INTERNATIONAL LAW - Corthay, Eric (UI Scholars Hub, 2015)
From the Sahel-Sahara region to Afghanistan, from Syria to the Philippines, the international community has been witnessing, for a number of years now, the establishment of military training and support partnerships, the launch of joint military operations and the formation of international coalitions which have had a recent upsurge, all of these regional having been specifically designed to fight against and eliminate the terrorist scourge. These different forms of military cooperation have been justified either by a consent or request from the territorial State, by the right of self-defense, or even by an authorization from the UN Security Council. This article’s purpose is to analyze the legal framework within which the operations must fall in order for them to be lawful and their justifications to be valid. Through the analysis of doctrinal debates, actual State practice and the decisions of the International Court of Justice, this paper examines notably the criteria that make an intervention by invitation valid, the limitative conditions of invocation and implementation of the right of self-defense, and finally the original as well as the current mechanism of collective security that has led to the establishment of peace or multilateral operations.